Sharia Financial Inclusion Based on Local Cultural Values to Support the Sustainability of Small Traders' Businesses - Hanifuddin, Iza; Kasanah, Nur; Bianda, Ryan (Hikmatuna : Journal for Integrative Islamic Studies, 2025)
Sharia financial inclusion has significant urgency in economic and social development, especially in countries with a majority Muslim population. Small traders often face difficulties in obtaining financing to support and sustain the growth of their businesses. This descriptive qualitative research, employing an ethnographic approach, aims to document and explore Sharia financial inclusion initiatives carried out by Baitul Mal wa Tamwil Mandiri Mandiri Berkah Sejahtera Sharia (BMT MBS Sharia) in support of the sustainability of small trader businesses. Data collection techniques are through observation, interviews, and documentation. Data analysis involved data reduction, data presentation, and drawing conclusions. The results of the research show: 1) the implementation of financial inclusion carried out by BMT MBS Sharia by providing easy savings transactions with sharia contracts, implementing a pick-up system with a Jagongan communication pattern, giving direct prizes without drawing lots, and adjusting to the trading times of partners who use the Krempyeng market system in Javanese calendar market days,  2) BMT MBS Sharia adopts local cultural values because they are more acceptable and easy to adapt to the conditions of market traders, and 3) the impact of inclusion carried out by BMT MBS Sharia is that as many as 863 small traders from 15 traditional markets are disciplined in saving, no again trapped by loan sharks,  and has a priority to get a financing program from BMT MBS Sharia, and can set aside to share. In this way, the existence of BMT MBS Shariah, a micro-Shariah financial institution, can help small traders survive.